Freedom and reflection Hegel and the logic of agency - Yeomans, Christopher (New York : Oxford University Press, 2012)
While many interpreters hold that Hegel avoided the traditional problem of free will, Yeomans argues both that the problem is unavoidable, and that the two versions of the Logic fruitfully engage the tensions between explicability and both the control and alternate possibilities constitutive of free agency.
Also issued in print format.
Description based on online resource; title from PDF title page (viewed on Jan. 21, 2012).
Includes bibliographical references and index.
Keywords: Hegel, Georg Wilhelm Friedrich, -- 1770-1831.; Free will and determinism; Philosophy